The association of monthly, diurnal and circadian variations with suicide attempts by young people - Türkan Akkaya-Kalayci; Nestor D. Kapusta; Thomas Waldhör; Victor Blüml; Luise Poustka; Zeliha Özlü-Erkilic (BMC, 2017)
Abstract Background Different psychosocial factors might have an impact on suicidal behaviour and evidence shows that there may be an association between monthly, diurnal and circadian changes and suicidal behaviours. Methods In the present study we analysed retrospectively records of 2232 youth, who were treated in emergency units of state hospitals in Istanbul/Turkey after attempting suicide. Results The majority of the suicide attempters were females (81.6%). In both sexes, suicide attempts most frequently occurred at the beginning of the calendar week and between evening and midnight. Conclusions This study shows that suicide attempts in youth follow diurnal and circadian changes. As suicide attempts of youth most frequently occurred at the beginning of the calendar week and between evening and midnight, health services such as specialized counselling for youth should especially be available during this time.